Non-stop mRNA decay: a special attribute of trans-translation mediated ribosome rescue - Venkataraman, Krithika; Guja, kip; Garcia-Diaz, Miguel; Karzai, Wali (Frontiers in Microbiology, 2014)
Decoding of aberrant mRNAs leads to unproductive ribosome stalling and sequestration of components of the translation machinery. Bacteria have evolved three seemingly independent pathways to resolve stalled translation complexes. The trans-translation process, orchestrated by the hybrid transfer-messenger RNA (tmRNA) and its essential protein co-factor, SmpB, is the principal translation quality control system for rescuing unproductively stalled ribosomes. Two specialized alternative rescue pathways, coordinated by ArfA and ArfB, have been recently discovered. The SmpB-tmRNA mediated trans-translation pathway, in addition to re-mobilizing stalled translation complexes, co-translationally appends a degradation tag to the associated nascent polypeptides, marking them for proteolysis by various cellular proteases. Another unique feature of trans-translation, not shared by the alternative rescue pathways, is the facility to recruit RNase R for targeted degradation of nonstop mRNAs, thus preventing further futile cycles of translation. The distinct C-terminal lysine-rich (K-rich) domain of RNase R is essential for its recruitment to stalled ribosomes. To gain new insights into the structure and function of RNase R, we investigated its global architecture, the spatial arrangement of its distinct domains, and the identities of key functional residues in its unique K-rich domain. Small-angle X-ray scattering (SAXS) models of RNase R reveal a tri-lobed structure with flexible N- and C-terminal domains, and suggest intimate contacts between the K-rich domain and the catalytic core of the enzyme. Alanine-scanning mutagenesis of the K-rich domain, in the region spanning residues 735 and 750, has uncovered the precise amino acid determinants required for the productive engagement of RNase R on tmRNA-rescued ribosomes. Theses analyses demonstrate that alanine substitution of conserved residues E740 and K741 result in profound defects, not only in the recruitment of RNase R to res